Ecologia e fitossociologia da vegetação arbórea de um morro testemunho no Sul do Brasil - Fávero, Alessandro Abreu (2015)
The research evaluates the floristic, phytogeographic contingent, ecological structure descriptors, spatial phytosociology and composition of ecological guilds of trees in a testimony mountain, also examines the variables of altimetry and morphometry. It was obtained the abiotic and biotic data in 15 sample units (10 x 50m), arranged in continuous transects the top of the mountain to base, totaling 7.500m2 of sampling. Trees data were recorded with the circumference at breast height ≥ 15,7cm (1,30m above at ground level). Environmental variables were derived from altimetry (altitude, slope and level difference) and morphometry (rocky outcrop, vertical curvature, sun exposure and soil depth), besides vegetation density and gaps (canopy openness). This master s dissertation has three chapters. The first chapter characterizes the floristic and phytogeographical contingent of trees. The second chapter evaluates the biological diversity: species richness, diversity (alpha biological diversity indices) and dominance models (ranking of abundance); and examines the exploratory analysis of the relationships between species and environmental variables. The third chapter analyzes the spatial phytosociology and the composition of ecological guilds in different ecological zones in the mountain slope.